2007
DOI: 10.1093/hmg/ddm081
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide suggestive linkage of opioid dependence to chromosome 14q

Abstract: The genetic predisposition to addiction to opioids and other substances is transmitted as a complex genetic trait, which investigators are attempting to characterize using genetic linkage and association. We now report a high-density genome-wide linkage study of opioid dependence. We ascertained 305 DSM-IV opioid dependent affected sibling pairs from an ethnically mixed population of methadone maintained subjects and genotyped their DNA using Affymetrix 10K v2 arrays. Analysis with MERLIN identified a region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 67 publications
4
56
1
1
Order By: Relevance
“…We also detected significant association (p=0.0003 in the combined sample) of OD with a SNP (rs770124) in the neuron navigator 3 (NAV3) gene; neuron navigators are expressed predominantly in the nervous system and involved in axon guidance (Maes et al 2002). A SNP (rs8688) in the TTC9 gene on chromosome 14 was significantly associated with OD in our study (p=0.003 in the combined sample) and is located approximately 5 cM from a linkage peak for OD in an ethnically mixed sample from New York City (Lachman et al 2007). TTC9 encodes tetratricopeptide repeat domain 9, a hormonally regulated protein whose function is not yet clear.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We also detected significant association (p=0.0003 in the combined sample) of OD with a SNP (rs770124) in the neuron navigator 3 (NAV3) gene; neuron navigators are expressed predominantly in the nervous system and involved in axon guidance (Maes et al 2002). A SNP (rs8688) in the TTC9 gene on chromosome 14 was significantly associated with OD in our study (p=0.003 in the combined sample) and is located approximately 5 cM from a linkage peak for OD in an ethnically mixed sample from New York City (Lachman et al 2007). TTC9 encodes tetratricopeptide repeat domain 9, a hormonally regulated protein whose function is not yet clear.…”
Section: Discussionmentioning
confidence: 56%
“…A genome-wide linkage scan detected regions harboring genes for cocaine dependence (CD) on chromosomes 3 and 10, and for cocaine-induced paranoia (CIP) on chromosome 9 . Regions on chromosome 17 showed significant evidence of linkage to opioid dependence (OD) in a recent study , and chromosome 14q showed suggestive linkage for OD in an ethnically mixed population (Lachman et al 2007). By comparison, a larger number of studies focused on alcohol dependence (AD) have identified linkage to several regions on chromosomes 1, 2, 4, 7, and 11 (reviewed by Dick and Beirut, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…45,48 NRXN3 polymorphisms have been linked with alcohol dependence, and NRXN3 has also been associated with nicotine and opiate dependence, the wide diversity of variants, brain regions and circuits are underreported at present. [49][50][51] NRXN3 has not been reported in SZ to date to our knowledge. Thus, the role of NRXN3 in synaptogenesis and its interaction with neuroligins in specific neuronal circuits may potentially increase the risk for SZ.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, Lachman et al 41 reported a linkage study of opioid dependence in a cohort of 591 subjects comprising 296 'subject-described' families. The variants we found to be significantly associated with heroin addiction are not on the same chromosome as the two linkage peaks reported by Lachman and co-workers.…”
Section: Discussionmentioning
confidence: 99%
“…Microarrays have been used extensively in the study of cancer to identify variants associated with disease 40 and, recently, for linkage analysis of opioid dependence. 41 The only other published microarray study to identify variants associated with drug and alcohol addiction have used pooled but not individual samples and the 1494, 42 10 000, 43 100 000, 44,45 and 500 000 single nucleotide polymorphism Affymetrix GeneChips. 45 In this study, we have used Affymetrix 10K GeneChips to locate and identify genes that may be associated with vulnerability to develop heroin addiction.…”
Section: Introductionmentioning
confidence: 99%